Structural steel designer's handbook / editors: Roger L. Brockenbrough, Frederick S. Merritt - Brockenbrough, Roger L.; Merritt, Frederick S. (McGraw-Hill, 1999)
If it has anything to do with the design of steel structures, you'll find it here, in the Structure Steel Designer's Handbook.